Human prolyl hydroxylase domain 2 reacts with O 2 and 2-oxoglutarate to enable formation of inactive Fe(III).2OG.hypoxia-inducible-factor α complexes - Fiorini, G; Marshall, SA; Figg, WD; Myers, WK; Brewitz, L; Schofield, CJ (Nature Research, 2024)
Hypoxia inducible transcription factors (HIFs) mediate the hypoxic response in metazoans. When sufficient O2 is present, Fe(II)/2-oxoglutarate (2OG)-dependent oxygenases (human PHD1-3) promote HIFα degradation via prolyl-hydroxylation. We report crystallographic, spectroscopic, and biochemical characterization of stable and inactive PHD2.Fe(III).2OG complexes. Aerobic incubation of PHD2 with Fe(II) and 2OG enables formation of PHD2.Fe(III).2OG complexes which bind HIF1-2α to give inactive PHD2.Fe(III).2OG.HIF1-2α complexes. The Fe(III) oxidation state in the inactive complexes was shown by EPR spectroscopy. L-Ascorbate hinders formation of the PHD2.Fe(III).2OG.(+/-HIFα) complexes and slowly regenerates them to give the catalytically active PHD2.Fe(II).2OG complex. Crystallographic comparison of the PHD2.Fe(III).2OG.HIF2α complex with the analogous anaerobic Fe(II) complex reveals near identical structures. Exposure of the anaerobic PHD2.Fe(II).2OG.HIF2α crystals to O2 enables in crystallo hydroxylation. The resulting PHD2.product structure, manifests conformational changes compared to the substrate structures. The results have implications for the role of the PHDs in hypoxia sensing and open new opportunities for inhibition of the PHDs and other 2OG dependent oxygenases by promoting formation of stable Fe(III) complexes.